Effect of intravitreal dexamethasone implant on the contralateral eye in recalcitrant radiation maculopathy - Gulati, Srishti Kamalmani (Oman J Ophthalmol, 2019)
Radiation maculopathy, a subset of significant radiation retinopathy, is one of the most common causes of visual loss following localized, regional, or whole-brain radiotherapy. Ozurdex (Allergan Inc., Irvine, CA, USA), a sustained-release intravitreal implant of 0.7 mg dexamethasone, has been used as an off-label treatment for treating recalcitrant radiation maculopathy. However, to the best of our knowledge, the beneficial effect of intravitreal dexamethasone in the contralateral eye in a patient with radiation maculopathy has not been described in the literature so far. In this case report, we report the efficacy of dexamethasone 0.7 mg intravitreal implant in recalcitrant radiation maculopathy which was refractory to intravitreal bevacizumab therapy. The patient showed good anatomical and functional outcomes in both the eyes after unilateral injection of intravitreal dexamethasone as evident by optical coherence tomography scans and fundus fluorescein angiography. It is noteworthy that the contralateral was not treated for 4 years. The case reveals systemic exposure of dexamethasone after intravitreal injection by demonstrating the bilateral effect after unilateral injection of intravitreal dexamethasone